DEIXIS in Luca Movie Script - Nuralisah, Fitra; Rosmawati, Rosmawati; Abeng, A. Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This research studied the use of deixis in the script of the animated Luca movie. This research identified and analyzed the various types of deixis present in the dialogue, and explored their functions. A qualitative descriptive method was involved in this research. The writer drew on a comprehensive analyzes of the Luca movie script, focusing on how deixis contributes to character interactions and the overall storytelling and only focusing to the main character. The findings revealed that deixis played a crucial role in establishing relationships between characters and their environment, enhancing the listeners’ understanding of the plot and emotional undertones. This research contributes not only to the field of pragmatics and linguistics but also offers insights for further research on language use in cinematic texts. The writer found that all of various types of deixis, to comperhand the contents of utterances or texts. The function of deixis in communication was that it understood the idea that understanding language required more than just knowledge of words and grammar; it necessitated an awareness of the context in which language was used